Short children born small for gestational age (SGA) : adrenarche, pubarche, gonadal function, pubertal development, food intake, quality of life and effects of growth hormone treatment - Boonstra, Venje (nakladatel není známý, 2005)
The study focuses on infants small for gestational age and how SGA influences children ́s later development. Written for professional public.
Keywords: vývoj dítěte; velikost těla; hormonální substituční terapie; genetika, lékařská genetika; Child; Infant, Small for Gestational Age; Body Size; Hormone Replacement Therapy; pediatrie; dítě; puberta; Child Development; Puberty; perinatologie a neonatologie; hypotrofický novorozenec